Terrorist Recognition Handbook : A Practitioner's Manual for Predicting and Identifying Terrorist Activities - Nance, Malcolm W. (Boca Raton, London CRC Press, Taylor and Francis Group, 2008)
Written by a 20-year veteran of the U.S. intelligence community, this second edition reflects the latest geopolitical factors affecting global terrorist incidents and regional insurgencies. A new section includes an analysis of transformations within Al Qaeda, coverage of the modern insurgency, and new global and regional terrorist groups. Completely updated, the section on terrorist tactics reveals the latest trends and attack methods and includes a new chapter on previously unseen suicide bombings. This book is an invaluable training tool on how to identify an attack; how to mitigate damage from successful attacks; and how to recognize the various stages of developing terrorist plots.
Include Index, Bibliography, Illustrations and Appendix.
Keywords: Terrorism